THE PAEDIATRIC OBSERVATION PRIORITY SCORE (POPS): A USEFUL TOOL TO PREDICT LIKELIHOOD OF ADMISSION FROM THE EMERGENCY DEPARTMENT. Issue 10 (7th September 2013) - Kelly, J; Rowland, A G; Cotterill, S; Lees, H; Kamara, M
Abstract : Objectives & Background: No specific early warning score universally validated for use in all children presenting to the Emergency Department (ED) exists. POPS is a novel aggregate scoring system, designed for ED use. Methods: Prospectively collected physiological and observational data were used to calculate POPS on 2068 patients aged under 16 presenting over one month to a UK District General Hospital Paediatric ED. Logistic regression was used to investigate the effect of POPS at first presentation on admission to hospital within the subsequent 72 hours. Results: 46% of patients were diagnosed with trauma and 54% with a medical condition. Mean age was 5.6 years (SD 4.6). 15.3% were admitted on first presentation. 76 re-presented within 72 hours of discharge from the ED and 19.7% were admitted. The mean POPS on first presentation was 0.87 (SD 1.58) overall (medical patients 1.03 (SD 1.70), trauma patients 0.68 (SD 1.41), p<0.001). POPS had a statistically significant positive effect on admission. A one point increase in POPS was associated with a 70% increase in the odds ratio (OR) of admission (p<0.001), with an area under the ROC of 0.72 (medical patients OR 1.67, area under ROC 0.73, p<0.001; trauma patients OR 1.77, area under ROC 0.69, p<0.001). The sensitivity and specificity of POPS to predict admission likelihood were: POPS≥2 (sensitivity 50%, specificity 85%), POPS≥3 (sensitivity 36%, specificity 93%). Conclusion: POPS is a useful tool to predict the admission likelihood from the ED. POPS≥2 correctly predicts 50% of children who should be admitted and 85% of children who should be discharged. Multi-centre validation would help to refine POPS, increasing its sensitivity and specificity to admission likelihood, to improve the safety of discharge decisions and healthcare resource utilisation.